Jigsaw Cooperative Learning: Boosting Grade III Reading Skills: Peningkatan Kemampuan Membaca Awal pada Siswa Kelas III: Dampak Pembelajaran Kooperatif Jigsaw. - Najunda Sari; Vevy Liansari (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative pre-experimental study aimed to investigate the effect of the Jigsaw Cooperative Learning model on the development of beginning reading skills in grade III students at an elementary school in Buduran, Sidoarjo. The study employed a saturated sampling technique, with a sample size of 20 students. The research instrument consisted of a descriptive question test, and the analysis involved a paired sample t-test for hypothesis testing. The results indicated a significant improvement in beginning reading skills after implementing the Jigsaw Cooperative Learning model, as evidenced by the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). The findings emphasize the positive impact of cooperative learning approaches in fostering reading proficiency among young learners, highlighting the importance of implementing such strategies in educational settings. Highlights: Cooperative learning: Enhancing reading skills through collaborative and interactive learning. Beginning reading: Investigating the impact of Jigsaw Cooperative Learning on early literacy development. Grade III students: Examining the effectiveness of cooperative learning in the context of primary education. Keywords: Jigsaw Cooperative Learning, Beginning Reading, Grade III Students, Quantitative Approach, Pre-experimental Design